Regional Cooperation on Rice Commodity to Achieve Food Security: Asean Case Study - Hanni Rizki Daliani; Siska Amelia; Siti Atikah Suri; Anita Safitri; Arini Nasihah; Meliana Meliana; Dwi Hasmidyani; Muhammad Akbar Budiman (Pijar Pustaka Widyadhana, 2024)
Food security remains a major concern among ASEAN countries, with rice an important commodity. Rice production is vulnerable to climate change, which causes production declines and price spikes. ASEAN is committed to strategic cooperation to protect rice supplies and prevent food crises, as well as increasing production and stabilizing supply through collaborative initiatives. This study uses qualitative methods and descriptive analysis in literature studies to explore the implementation of ASEAN regional cooperation on rice commodities. Secondary data is used to understand the impact of rice commodities on food security in the ASEAN region. Through a descriptive analytical approach, this research aims to provide an accurate picture of the relationship between regional cooperation and rice commodity management in ASEAN. The results of this research indicate that ASEAN rice market integration is important to reduce price risks for farmers and improve food security. The establishment of a rice futures market can help manage risks and ensure stable prices. Regional cooperation and harmonization of rice standards are needed, as well as improved infrastructure and financial support for farmers.